A Diallel Cross-Based Analysis of the Genetic Basis of Pod Quality and Pod Yield in Snap Bean - Njau, Serah N.; Arunga, Esther; Otsyula, R (UoEm, 2024)
Snap bean (Phaseolus vulgaris L.) is among the leading vegetables in Kenya that is mainly grown for export with the potential to increase household income. There are few programs in Kenya that focus on breeding new cultivars for increased production. The development of snap bean varieties that are resilient to the changing climate is crucial for sustainable agriculture in Kenya. To achieve this, knowledge of gene action, trait expression, and heritability is vital in effective breeding for quantitative traits like pod quality and yield. A study was conducted to investigate the inheritance of pod quality and yield traits in snap beans, which can inform the breeding of snap beans. A half diallel cross involving two indeterminate dry beans (G2333 and MCM 5001) and five determinate snap beans (Amy, Moonstone, Seagull, Serengeti and Vanilla) varieties was conducted. Data on pod traits (pod weight per plant, pod number per plant, pod length, pod diameter, pod wall fiber and pod suture string) were collected from 21 F1s and 7 parents grown in two locations (Embu and Kirinyaga Counties) in Kenya. The results showed significant genotypic and environmental effects (P < 0.001) for all traits, with significant genotype by environment (G × E) interactions for most traits. Additionally, general combining abilities (GCA) and specific combining abilities (SCA) were significant for all traits evaluated. The significance of GCA and SCA indicated the importance of both additive and non-additive gene effects in controlling the traits, although the additive gene effects were predominant. The study revealed that Vanilla and Serengeti had the highest GCA estimate for pod quality traits, while G2333 and MCM5001 had the highest GCA estimate for pod yield traits. Snap bean pod yield and quality are quantitative traits controlled by multiple genes and influenced by the environment. Therefore, the predominance of additive gene effects suggests that selection for these traits in segregating generations could yield satisfactory gains. The results of this study could impact the development of snap bean varieties that are more resilient to the effects of climate change. Thus, improving the sustainability and productivity of the agriculture sector in Kenya.
Article
Keywords: Snap bean; GCA; SCA; Gene action; Heritability; Combining ability